2012
DOI: 10.1590/s0037-86822012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory alterations in dogs naturally infected by Leishmania chagasi

Abstract: Introduction: Canine visceral leishmaniasis (CVL) is a zoonotic disease with different clinical manifestations. Parasitism often occurs in bone marrow, but changes have been observed in peripheral blood and serum biochemical parameters. The aim of this study was to evaluate the hematological and biochemical parameters in dogs naturally infected by Leishmania chagasi. Methods: Eighty-five adult dogs of both sexes and various weights and ages from the Zoonosis Control Center of Fortaleza (CCZ) were used, selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 16 publications
7
33
1
17
Order By: Relevance
“…Symptomatic dogs demonstrate severe anemia, with a significant decrease in the number of erythrocytes, hemoglobin, and hematocrit (Reis et al, 2006;Freitas et al, 2012). Similarly, in this study, decreases in erythrocyte, hemoglobin, and hematocrit level due to lipid peroxidation development in case 3 were detected before treatment regarding the infection.…”
Section: Resultssupporting
confidence: 74%
“…Symptomatic dogs demonstrate severe anemia, with a significant decrease in the number of erythrocytes, hemoglobin, and hematocrit (Reis et al, 2006;Freitas et al, 2012). Similarly, in this study, decreases in erythrocyte, hemoglobin, and hematocrit level due to lipid peroxidation development in case 3 were detected before treatment regarding the infection.…”
Section: Resultssupporting
confidence: 74%
“…The researchers reported that the IFA technique was a quite sensitive and specific test for the determination of leishmaniasis, and upon evaluating the clinical findings and laboratory results together, the titrations between 1/40 and 1/1024 were diagnostic in seropositive patients and the titers above 1/40 were sufficient for the diagnosis of canine leishmaniasis (Freitas et al 2012). In our study, titers of 1/64 and above are accepted as positive.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anemia, neutropenia, thrombocytopenia, uremia, hyperproteinaemia, hypergammaglobulinemia, hyperalbuminemia, an increase in ALT, GGT, LDH and ALP levels, in urea and creatine level can be listed as mild or severe proteinuri a laboratory findings. The clinical findings may show variability depending on the course, phase and severity of the disease in Canine visceral leishmaniasis (CVL) (Freitas et al 2012, Taher et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mancianti et al (1988), the host-parasite interaction may result in different clinical responses, which would explain the different responses observed. However, it is believed that hyperproteinemia in VLG dogs, as observed by Torrent et al (2005) and Silvestrini et al (2012), is due to hypergammaglobulinemia (Freitas et al, 2012), which in turn is due to a polyclonal lymphocyte response caused by the infection (Reis et al, 2009). …”
Section: Discussionmentioning
confidence: 99%